INSTITUTIONAL BUILDING DALAM PEMBANGUNAN PERTANIAN - Hanifah Ihsaniyati (Universitas Sebelas Maret, 2008)
Increasing agriculture product by farmers have not been followed yet by increasing farmers income and welfare significantly.Institutional building become important thing for agricultural development that the most actors are small farmer and peasant. The institutions are farmer economic institution and agricultural extension institution. They must can be accessed by farmer to increase their welfare. Therefore there are needed inceasing acess ofits institutions by farmers.